Upcycling of plastic waste into multi-walled carbon nanotubes as efficient organic dye adsorbent - Gaceva, Gordana Bogoeva (Acta chimica slovenica, 2025)
Multi-walled CNTs with an average diameter of about 80 nm, a length of several micrometers and surface area (SBET) of 100 m2 g–1 were obtained by pyrolysis of low-density polyethylene waste. The potential of the resulting MWCNTs material to purify water containing organic dyes was tested with Bezaktiv Blau HE-RM (BB) and Bezaktiv Rot S-3B (BR) reactive dyes. 200 mg L–1 MWCNT material was used to follow the adsorption of 30 mg L–1, 40 mg L–1, 50 mg L–1 and 60 mg L–1 BB and BR at pH 3 and a temperature of ~25 °C. The results have shown that this material has a high potential as a sorbent, and its adsorption capacity of 257 mg g–1 (for Bezaktiv BlauHE-RM) and 213 mg g–1 (for Bezaktiv Rot) is close to some commercial MWCNTs and functionalized MWCNT-based adsorbents. The adsorption process was very fast, reaching 80–90% of the dye removal in 10–15 minutes, and the equilibrium time was reached in 40–60 minutes. The adsorption isotherm showed that the Langmuir model was more suitable than the Freundlich model for describing the adsorption properties of the pollutants.
Keywords: adsorpcija; adsorption; anionic dyes; anionska barvila; carbon nanotubes; karbonske nanocevke; recikliranje plastičnih odpadkov; upcycling plastic waste